Genome-wide identification, phylogenetic and expression pattern analysis of GATA gene family in Cerasus humilis - Pan, Meitong; Yue, Chenzhuo; Jiang, Shan; Ma, Junbai; Ma, Lengleng; Kong, Lingyang; Ling, Yang; Ma, Wei; Ren, Weichao; Liu, Xiubo (Frontiers in Plant Science, 2025)
IntroductionThe transcription factor GATA plays a pivotal role in plant growth, physical and metabolic functions, and responses to changes in the environment. After the completion of the Cerasus humilis genome, investigations into its GATA gene family were not pursued.MethodsOur research team identified the GATA gene’s bioinformatics techniques, analyzed its structural characteristics and evolutionary trajectory, and investigated its expression patterns among various subfamilies.ResultsIn the C. humilis genome,20 ChGATAs are divided into four unique subgroups distributed over 7 chromosomes. Collinearity analysis showed 7 pairs of segmental duplications and 2 pairs of tandem repeats. The duplication of these fragments is vital for the development of the ChGATA family. The evolutionary connection between C. humilis and the Malus pumila GATA gene family is more evident than with Oryza sativa. Moreover, the promoter region of the ChGATA gene family contained cis-acting elements linked to stress, hormones, and plant growth. The transcriptome heatmap showed that the expression of the ChGATA was specific under alkali stress, and ChGATAs in the same subpopulation would also show different expression patterns. qPCR analysis showed that most of the screened ChGATAs first decreased and then increased with time. In addition, the dual luciferase assay and protein interaction prediction showed that ChWRKY29 could activate the expression of the differentially expressed gene ChGATA14 in response to alkali stress, and ChGATA14 was at the core of the protein interaction network and had a strong interaction with ChGATA2 and ChGATA16.DiscussionThis study laid a theoretical and scientific foundation for further studies on the biological function of ChGATA.